Revitalisasi Spiritualitas Ekologi Perspektif Pendidikan Islam - Eko Asmanto (Universitas Darussalam Gontor, 2015)
Amid the growing coalescence between the religion and ecology movement, religion and science, spirituality and ecology, the voice of Muslim thinking that care for the earth and its people is rising. While the Islamic position on the environment is not well-represented in the eco-theology discourse, it advances an environmental imaginary which shows how faith can be harnessed as a movement for social change. This article will draw upon field research which synthesized the Islamic ecological spirituality (eco-spirituality) from sacred texts, traditions, and contemporary thought, and illustrated how this spirituality is enlivened in the educational landscape of Islam. Knowledge of the relationship between human beings and the natural world, of the function upon which the nature was created, and of the function right living, is essential in this educational project, and the global eco-Islamic movement toward the eco-friendly community to environment. Despite the manifestation of environmental education activities in educational establishment, which are generally patterned Islamic education today is not representative of the holistic, integrated, and comprehensive educational philosophy of Islam. As contemporary world today, such as the environmental question, act as an impetus to encourages, to develop even to build a pedagogy which endeavours to be true to the religious traditions, values, and ethics of Islam, while also displaying the transformation of Islamic faith. Of course, many of them based their life, and lifestyle decisions on the teachings of Islam, and are showing the relevance of traditional resources and greatest life challenges facing humanity today; namely “save our nature”.